Exploring the effect of different tea varieties on the quality of Lu’an Guapian tea based on metabolomics and molecular sensory science - Wanzhen Feng; Huan Zhou; Zhichao Xiong; Caiyan Sheng; Dongzhou Xia; Jixin Zhang; Tiehan Li; Yuming Wei; Wei-Wei Deng; Jingming Ning (Food Chemistry: X, 2024)
Lu’an Guapian (LAGP) tea is one of the most famous teas in China. However, research on its suitable processing varieties is still lacking. This study analyzed the quality of LAGP tea made from three different tea varieties, namely, ‘Anhui1’ (AH1), ‘Quntizhong’ (QTZ), and ‘Shuchazao’ (SCZ), using molecular sensory science and metabolomics techniques. The results showed that AH1 had a strong floral aroma and the strongest umami flavor, while QTZ had a distinct roasted aroma and a mellow taste. SCZ had a cooked corn-like aroma and the highest bitterness and astringency owing to the high tea polyphenol contents and low free amino acid contents. The study also identified 12 key aroma-active compounds, with trans-beta-ionone and 2-ethyl-3,5-dimethyl-pyrazine contributing the most to floral and roasted aromas, respectively. The results of this study provide a theoretical and practical basis for selecting and breeding high-quality varieties of LAGP tea and stabilizing its quality.